Sistem Monitoring Kualitas Air dan Pakan Otomatis Pada Akuarium Ikan Mas Koki Terintegrasi IoT - Lestari, Dewi; Yuniarti, Elvan; Dinda Sari, Yayang (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
Water is a living medium for goldfish, which greatly influences their lives. Water quality as a living medium for fish greatly influences the growth and development of goldfish; therefore, water quality must meet the needs of goldfish. Several water quality parameters that greatly influence fish life are temperature, degree of acidity (pH), and solid substances dissolved in water (TDS). The aim of this research is to design a monitoring system capable of measuring temperature, degree of acidity (pH), and solid substances dissolved in water based on the Internet of Things. This tool is used for an Internet of Things-based water quality monitoring system in goldfish aquariums, where the results obtained will be sent via smartphone to the Blynk application. And it can also provide food automatically and provide notifications if the water becomes cloudy. This tool is designed using an Arduino Uno, a Wemos D1 R2 controller, and sensors used to measure each parameter, namely the DS18B20 sensor, pH sensor, and TDS sensor. Then the feeder uses a servo to open the feed and an RTC as a timer. The results of this research conclude that the calibration results for the DS18B20 sensor have an average accuracy rate of 99% with a sensor error percentage of 1%, the pH sensor has an accuracy rate of 98.7% with an error percentage of 1.3%, and the TDS sensor has an accuracy rate of 94.59% with an error percentage of 5.41%.